Implementasi Model Pembelajaran Snowball Throwing Dengan Media Teka-Teki Silang Untuk Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Kelas Xi Iis 1 Di SMA Negeri 5 Purworejo - Lestari, Prawidya; Sabiti, Nurul (IAINU Kebumen, 2022)
The purpose of this study is to know the implementation of snowball throwing method with crossword puzzle media to improve students’ learning motivation in Religion and Moral Education of Class XI IIS 1in SMA Negeri 5 Purworejo. The type of research used in this study is Classroom Action Research. The subject of this study are students of Class XI IIS 1 in SMA Negeri 5 Purworejo and the object used in this study is students’ learning motivation. In order to get the result of the study, the writer used several techniques such as observation, interview, and questioner. The result of this study is as stated here, (1) snowball throwing method with crossword puzzle media in Religion and Moral Education is suitable to be applied on tarikh aspect, (2) snowball throwing method with crossword puzzle media can improve students’ learning motivation, (3) snowball throwing method with crossword puzzle media has advantages and disadvantages.